2020
DOI: 10.1039/d0fo00627k
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of β-lactoglobulin–epigallocatechin gallate interactions: the antioxidant capacity and effects of polyphenols under different heating conditions in polyphenolic–protein interactions

Abstract: A β-Lg-EGCG covalent conjugate is formed by linking the amino group of a lysine residue and EGCG; the antioxidant capacity of EGCG induced by β-Lg–EGCG covalent conjugates causes a significant decrease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…Qie et al. (2020) revealed that EGCG inhibited the heat‐induced decrease in the β‐Lg ‐SH level. This may be ascribed to the fact that ARR protects the sulfhydryl group against the heat‐induced oxidation reactions and amyloid aggregation of β‐Lg (Keppler et al., 2019; Muhammad et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Qie et al. (2020) revealed that EGCG inhibited the heat‐induced decrease in the β‐Lg ‐SH level. This may be ascribed to the fact that ARR protects the sulfhydryl group against the heat‐induced oxidation reactions and amyloid aggregation of β‐Lg (Keppler et al., 2019; Muhammad et al., 2009).…”
Section: Resultsmentioning
confidence: 99%
“…ECG and EGCG binding with β‐Lg also increased the α‐helix ratio (Kanakis et al., 2011; Zhang et al., 2017). Although EGCG binding reduced the β‐sheet ratio in the β‐Lg (Qie et al., 2020), this value was increased by Mv‐3‐O‐glucoside binding (He et al., 2016), while the turn and random coil structure ratios in the β‐Lg were increased and reduced, respectively (Figure 4b). However, Mv‐3‐O‐glucoside and EGCG binding to β‐Lg decreased the turn and random coil ratios (He et al., 2016; Qie et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, milk products are also a special industry with great attention in the agriculture and animal husbandry industry chain. In the process of food processing, β-LG is also widely added to increase nutrition of foods, increasing the risk of exposure to β-LG in people with milk allergies [ 7 9 ]. Therefore, it is necessary to develop a convenient, accurate, effective and specific analytical method to monitor the content of β-LG in milk products, which beneficial to protect consumers from the threat of allergies.…”
Section: Introductionmentioning
confidence: 99%